Population dynamics and description of larva and pupa of Cyclocephala tucumana Bréthes, 1904 in West-Central Brazil, and remarks on immatures of other Cyclocephala species (Coleoptera: Scarabaeidae: Dynastinae) - Fuhrmann,Juares (2019)
ABSTRACT Some species of Cyclocephala Dejean, 1821 (Coleoptera, Scarabaeidae, Dynastinae, Cyclocephalini) were reported as crop or pasture pests. Within this genus, Cyclocephla tucumana Bréthes, 1904 was noticed in cultivated areas in South Brazil, 2009 − 2010. Other study found larvae of the species associated with pastures in Aquidauana, Mato Grasso do Sul State (MS), 2009. In the present study, larvae of C. tucumana were collected in pasture areas from August 2015 to July 2016, in Cassilândia, MS. The material was reared in laboratory for the description of immatures, and the regional population was studied to clarify its dynamics. Immatures were abundant throughout the years and are described for the first time. Taxonomic discussion, updated key to larvae and pupae, and a teratological note are also added.